The Effect of Tax Minimization, Debt Covenant, and Foreign Ownership on Transfer Pricing - Ratnosari, Devi; Nugroho , Sasmito Widi; Tohari, Hamim (Indonesian Scientific Publication, 2024)
The study aims to review, test, and analyze the effect of tax minimization, debt covenants, and foreign ownership on transfer pricing. This research focuses on mining companies listed on the Indonesia Stock Exchange (IDX) during the 2018-2022 period, with a population of 37 companies and a sample of 11 companies selected through purposive sampling technique. Data analysis was conducted using multiple linear regression through the SPSS version 25 application after going through classical assumption tests such as normality, multicollinearity, heteroscedasticity, autocorrelation, coefficient of determination (R2), and t test. The results of this study indicate that tax minimization, debt covenant, and foreign ownership have a positive and significant effect partially on transfer pricing. Overall, these three variables make a significant contribution to transfer pricing. This research is expected to be a reference for readers who are interested in understanding more about transfer pricing taxation. It is recommended for future researchers to expand the scope of the year and object of the research, as well as add or change independent variables that have the potential to affect transfer pricing.